1973
DOI: 10.1136/gut.14.9.701
|View full text |Cite
|
Sign up to set email alerts
|

Cell kinetics in flat (avillous) mucosa of the human small intestine

Abstract: SUMMARY A new method for the analysis of small-intestinal crypt-cell kinetics using routine peroral diagnostic biopsies is described. Untreated patients with childhood and adult coeliac disease and adults with the gluten-sensitive enteropathy of dermatitis herpetiformis were studied, together with groups of adult and childhood controls. In the classical flat avillous mucosae the increase in crypt size was found to be three-dimensional. The number of proliferating cells per crypt was shown to be markedly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…Furthermore, we demonstrated that the number of enteroblasts per 100/~m crypt length is not influenced by the treatment, and concluded that hyperplasia is the predominant mechanism for the enlargement of this compartment. A similar transformation of the crypt region is observed in coeliac disease [28] and in the experimental blind loop syndrome [21], both situations also being characterized by increased proliferation. Thus, it seems likely that a three-dimensional increase in crypt size and a concomitant decrease in the number of crypts per unit serosal area is a specific feature when cell production rate is altered in this way.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, we demonstrated that the number of enteroblasts per 100/~m crypt length is not influenced by the treatment, and concluded that hyperplasia is the predominant mechanism for the enlargement of this compartment. A similar transformation of the crypt region is observed in coeliac disease [28] and in the experimental blind loop syndrome [21], both situations also being characterized by increased proliferation. Thus, it seems likely that a three-dimensional increase in crypt size and a concomitant decrease in the number of crypts per unit serosal area is a specific feature when cell production rate is altered in this way.…”
Section: Discussionmentioning
confidence: 61%
“…l5 For estimation of the size of the proliferative compartment (PC) a graphical method was used, determining the 50% peak value of the mitotic index distribution curve. 16 sectioned crypts and cells per circumference of 150 cross sectioned crypts. At the time of death, blood was sampled for gastrin radioimmunoassay.…”
Section: Cell Proliferation Studiesmentioning
confidence: 99%
“…Generally, gut inflammatory reactions to bacterial pathogens and parasites in the colon lead to increased epithelial proliferation [31,32]. Celiac disease is the classical bowel disease associated with increased epithelial proliferation, where the pathology involves a Th1/IFN-g response to gluten and massively increased cell proliferation in the crypts of Lieberkühn of the upper small bowel [33,34]. Therefore, the statement in the paper under evaluation that "Prolonged intestinal inflammation inhibits IEC (intestinal epithelial cell) proliferation and promotes cell death" is not generally sustainable.…”
Section: Discussionmentioning
confidence: 99%